TEST OF A QUADRATIC RELATIONSHIP BETWEEN AGGREGATE OUTPUT AND GOVERNMENT DEBT IN HUNGARY - Hsing, Yu (The European Journal of Applied Economics, 2018)
The study which applies extended model of aggregate demand and aggregatesupply (AD/AS) and uses a quarterly sample during the periodfrom 2001 (Q1) till the last quarter of 2015, has shown that real GDPin Hungary exhibits a bell-shaped quadratic relationship with governmentdebt as a percent of GDP (DY), direct relationship with the realeffective exchange rate (ER), stock market price (SP) and the real crudeoil price (OP), and an inverse relationship with the real governmentbond yield (IR) and the expected inflation rate (EI). The critical value ofgovernment debt as a percent of GDP is estimated to be 69.22%, whichis higher than the EU criterion of 60.00% but less than the threshold of90.00% proposed by Reinhart and Rogoff (2010).
Keywords: government debt as a percent of GDP; real exchange rates; interest rates; stock prices; oil price